Trends of Planetary Boundary Layer Height Over Urban Cities of China From 1980–2018 - Huo, Yanfeng; Wang, Yonghong; Paasonen, Pauli; Liu, Quan; Tang, Guiqian; Ma, Yuanyuan; Petaja, Tuukka; Kerminen, Veli-Matti; Kulmala, Markku (Frontiers in Environmental Science, 2021)
Boundary layer height (BLH) is an important parameter in climatology and air pollution research, especially in urban city. We calculated the BLH with a bulk Richardson number (Ri) method over urban cities of China during 1980-2018 using European Centre for Medium-Range Weather Forecasts (ECMWF) ERA-interim data after carefully validation with sounding data obtained from two meteorology stations in eastern China during 2010-2018. The values of BLH between these two types of data have correlation coefficients in the range of 0.65-0.87, which indicates that it is reasonable to analyze long-term trends of the BLH from ERA data sets. Using ERA-interim calculated BLH, we found that there is an increasing trend in the daytime BLH in most cities of eastern China, particularly during the spring season. A correlation analysis between the BLH and temperature, wind speed, relative humidity and visibility revealed that the variability in meteorological parameters, as well as in aerosol concentrations over highly polluted eastern China, play important roles in the development of the BLH.